Respons Pertumbuhan dan Produksi Brokoli Terhadap Pemberian Pupuk Kandang Ayam dan Jamur Pelarut Fosfat - Dedi Yanto Filo Pinem; T. Irmansyah; Ferry Ezra Sitepu (Universitas Sumatera Utara, 2015)
This study aims to determine the growth and the production response of broccoli on application ofchicken manure and Phosphate Solubilizing fungi. This research was conducted in the field of BalaiPenyuluhan Pertanian (BPP) Kuta Gadung, subdistrict Berastagi Karo regency of North Sumatrawith altitude ± 1250 meters above sea level in January - April 2014 using a Randomized BlockDesign (RBD) factorial with 2 factors : chicken manure (0 kg , 3 kg , 6 kg ,9 kg per plot) and fungiphosphate solvent (10 ml , 20 ml , 30 ml per plant).The variable observations measured were plantheight , stem diameter , number of leaves , fresh weight per plant samples , selling fresh weight perplant sample and the number of chlorophylls. The results showed that the variable observationsresponse of broccoli plant height (cm) 6 weeks after plant ,broccoli stem diameter (mm) 6 weeksafter plant, number of leaves of broccoli plants (strands) 6 weeks after plant , fresh weight perbroccoli plant sample (g), selling fresh weight per broccoli plant sample (g) and the amount ofbroccoli chlorophylls was different significantly affected against chicken manure but nonsignificantly affect againts fungi phosphate solvent and both interactions.Keywords :Chicken Manure, Fungi Phosphate Solvent, Broccoli